Neuroinflammation as a factor of pathogenesis of glaucomatous optic neuropathy - T. A. Pavlenko; S. Yu. Petrov; E. N. Iomdina (Российский офтальмологический журнал, 2024)
The modern pathogenesis of the neurodegenerative process in glaucoma identifies several key risk factors for its development: ischemia/hypoxia, mitochondrial dysfunction, oxidative stress and neuroinflammation. An analysis of recent studies shows that in glaucomatous optic neuropathy, as in other neurodegenerative diseases, the immune system is involved in the pathological process, and immunoregulation is carried out mainly by retinal glial cells, microglia, astrocytes, Müller cells and the complement system. Chronic activation of glial cells caused by increased intraocular pressure in glaucoma can provoke a pro-inflammatory state at the retinal level, causing disruption of the blood-retinal barrier and death of retinal ganglion cells. The review presents pro-inflammatory markers of glaucoma, immunomodulatory and pro-inflammatory mediators, shows the role of a number of metalloproteinases and their tissue inhibitors, as well as pro-inflammatory cytokines in the development of glaucoma.